Penafsiran Ayat-Ayat Perdamaian Al-Qur'an: Studi Perbandingan Antara Tafsir Klasik dan Kontemporer dalam Konteks Perdamaian Global dan Kemanusiaan - Anisatul Fikriyah Aprilianti (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Amid escalating global conflicts and humanitarian crises, the Qur’an offers an enduring ethical foundation for building peace and upholding human dignity universally. This study seeks to address the central question: how are the Qur’anic verses on peace interpreted by classical and contemporary exegetes, and to what extent are these interpretations relevant in promoting global peace and humanitarian values today? The distinctiveness of this research lies in its comparative-transhistorical approach, which bridges the reformist perspectives of Muhammad ‘Abduh and Sayyid Quṭb with the humanistic approaches of Farid Esack and Khaled Abou El Fadl—an analytical framework rarely applied in previous Qur’anic exegesis studies. Employing a qualitative method through library research and thematic-comparative analysis, this study examines major exegetical works such as Tafsīr al-Manār, Fī Ẓilāl al-Qur’ān, Qur’an, Liberation, and Pluralism, and Reasoning with God. The findings indicate that classical exegetes emphasize moral reform, social harmony, and justice as the foundations of peace, while contemporary thinkers expand these interpretations toward universal ethical principles that support interfaith dialogue, social justice, and global solidarity. This study concludes that integrating both approaches produces a comprehensive Qur’anic paradigm of peace that is relevant to contemporary global challenges.